Process Equipment Procurement in the Chemical and Related Industries - Golwalkar, Kiran (Springer, 2015)
This concise volume explains when to procure new equipment, how to prepare specifications for floating inquiries, and guidelines for detailed technical discussions with vendors in the chemical and related industries. It covers the common equipment and supplies used in chemical plants, refineries-please delete reference to refineries, and effluent treatment facilities such as pumps, blowers, reactors, heat exchangers, waste heat recovery boilers, heat and acid resistant lining etc. The book serves as a checklist to the plant managements for procurement of the correct equipment in the most efficient timeframe insuring that projects are not delayed due to long time required for procurement of new equipment.